(untitled) (ARTEKS : Jurnal Teknik Arsitektur, 2022)
The study aims to determine the pattern and type permanence levels of the elements used to build the Kasongan area in the last 60 years. Permanence is an approach used to determine identity in the context of regional change. Kasongan is a rural-urban area with agrarian resources located between Bantul and Yogyakarta and influenced by urban globalization. This historic area is almost two centuries old and has developed into a village of pottery craftsmen. Adaptation to environmental and cultural changes after the 1960s made Kasongan transform from an agrarian village character to an industrial and then to a tourism village-town. Changes in this region can be seen in the building and area typology, which developed into a sustainable tourism area. The locus taken is a part of the Kajen and Beton Hamlet, which are indicated as early stages of growth and development direction for the Kasongan in the last few decades. The is a typo-morphological study carried out using a morphological mapping method and a regional typological process. The results found spatial patterns and types that (1) persisted as the initial identity, (2) changed, and (3) disappeared.